Disrupting the clock: meta-analysis of irregular night shifts and migraine, proposing shift work migraine disorder with chronobiology strategies - Woldeamanuel, Yohannes W.; Rahman, Ariana; Hyimanot, Esam T.; Chirravuri, Richa; Fani, Mahya; Javaheri, Elika D.; Welch, Madeline; Zhuang, Joyce; Mun, Chung Jung (Frontiers in Neurology, 2025)
BackgroundMigraine is linked to circadian rhythm disruptions, with morning attack peaks, circadian variations in trigeminal pain sensitivity, anterior hypothalamus involvement, and core circadian clock gene activity. Irregular night shift work, affecting up to 50% of the population, including new parents and students, causes significant circadian disruption. We hypothesize that irregular night shifts increase migraine prevalence compared to fixed schedules.MethodsA systematic review and meta-analysis of observational studies up to March 27, 2025, assessed migraine prevalence in irregular versus fixed night shift workers, searching Web of Science and PubMed with terms like “shift work” and “migraine” (PRISMA/MOOSE-compliant, PROSPERO: CRD420250654865). Study quality was evaluated using the Newcastle–Ottawa Scale (NOS). A random-effects meta-analysis calculated weighted odds ratios (ORs) for migraine prevalence.ResultsFrom 203 records, 13 high-quality cross-sectional studies (N = 38,798,271, 77% female, NOS 9–10) showed irregular night shifts significantly increased migraine odds (OR = 1.61, 95% CI: 1.27–2.04, p < 0.0001, I2 = 73%), with females at higher odds (OR = 2.02–4.21). Meta-regression linked higher female representation to increased migraine odds (β = 0.70, p = 0.0003, R2 = 50%). Irregular night shifts showed no association with tension-type headache (OR = 0.79, 95% CI: 0.43–1.45).ConclusionIrregular night shifts disrupt circadian rhythms, elevating migraine odds but not tension-type headache, suggesting fixed schedules may reduce the burden. Chronobiology-informed management, including slow-rotating schedules (≥5 days with rest days), delay-directed rotations, timed light exposure, and ambient temperature regulation, needs testing to prevent ‘Shift Work Migraine Disorder,’ a proposed distinct migraine subgroup.Systematic review registrationPROSPERO, CRD420250654865.